Strategi Perdagangan Internasional Indonesia di Nigeria (Studi Kasus Ekspor Produk Indomie) - Zaky, Shalahuddin; Aritonang, Novelya (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study discusses Indonesia's international trade strategy through the export of Indomie products in Nigeria. As one of Indomie's largest markets abroad, Nigeria is an important example in the analysis of the success of international marketing strategies. Using a descriptive qualitative method, this study analyzes strategies that include product adjustment, promotion, distribution, and strategic partnerships. The results of the study show that adaptation to local tastes, competitive prices, and collaboration through joint ventures are the main factors for Indomie's success in Nigeria. This study provides insight into the development of international trade strategies for Indonesian products in the global market.